Point-of-Care Testing to Guide Treatment and Estimate Risk Factors for Sexually Transmitted Infections in Adolescents and Young People With Human Immunodeficiency Virus in Eswatini. (13th February 2020) - Jasumback, Caitlyn L; Perry, Sarah H; Ness, Tara E; Matsenjwa, Martha; Masangane, Zandile T; Mavimbela, Mpumelelo; Mthethwa, Nobuhle; Dlamini, Lindokuhle; Mphaya, Joyce; Kirchner, H Lester; Mandalakas, Anna; Kay, Alexander W
Abstract: Background: The World Health Organization (WHO) estimates 127 million new cases of Chlamydia trachomatis (CT), 87 million new cases of Neisseria gonorrhea (NG), and 156 million new cases of Trichomonas vaginalis (TV) each year, which corresponds to 355 (219–606), 303 (216–468), and 243 (97.6–425) thousand disability-adjusted life-years. In low-resource settings, however, sexually transmitted infections (STIs) are treated syndromically and many individuals with asymptomatic infection may be missed, especially adolescents and young adults with human immunodeficiency virus (HIV). Methods: We enrolled patients aged 15–24 with HIV (N = 300) attending a family-centered HIV clinic in Mbabane, Eswatini. Participants completed a sexual history questionnaire and provided urine as well as oropharyngeal and/or vaginal swabs, if sexually active, for testing with Xpert CT/NG and TV tests. Analysis included bivariate and multivariate odds ratios and test sensitivity and specificity. Results: Sexually transmitted infection rates were highest (25.0%; 95% confidence interval [CI], 15.2–37.3) in females ages 20–24 who were ever sexually active. In patients with confirmed STIs, NG (15 of 32, 47%) was more common than CT (9 of 32, 28%) and TV (8 of 32, 25%). Syndromic screening alone had a sensitivity of 32.0% (95% CI, 14.9–53.3) and specificity of 86.0% (95% CI, 79.0–91.4) but varied by gender. The presence of an STI was associated with reporting new sexual partner(s) (OR = 2.6; 95% CI,  1.1–6.4), sometimes to never using condoms (OR = 4.2; 95% CI, 1.7–10.2), most recent sexual partner >25 years old (OR = 3.2; 95% CI, 1.3–7.9), and HIV diagnosis at age ≥15 years (OR = 3.4; 95% CI, 1.4–8.2). Conclusions: Syndromic screening alone performed poorly. Routine diagnostic testing significantly increases STI detection and should be considered in high-risk populations, such as adolescents and young adults with HIV. Abstract : In low-resource settings, like Eswatini, syndromically managing STIs vastly undertreats infected adolescents and young adults with HIV, fueling the spread of these infections. This study compares syndromic screening to diagnostic STI testing and treatment in Eswatini and estimates risk factors.